Comparative investigation on heterotrophic denitrification driven by different biodegradable polymers for nitrate removal in mariculture wastewater: Organic carbon release, denitrification performance, and microbial community - Feng, Yuna; Wang, Lu; Yin, Zhendong; Cui, Zhengguo; Qu, Keming; Wang, Dawei; Wang, Zhanying; Zhu, Shengmin; Cui, Hongwu (Frontiers in Microbiology, 2023)
Heterotrophic denitrification is widely studied to purify freshwater wastewater, but its application to seawater wastewater is rarely reported. In this study, two types of agricultural wastes and two types of synthetic polymers were selected as solid carbon sources in denitrification process to explore their effects on the purification capacity of low-C/N marine recirculating aquaculture wastewater (NO3--N 30 mg/L, salinity 32‰). The surface properties of reed straw (RS), corn cob (CC), polycaprolactone (PCL) and poly3-hydroxybutyrate-hydroxypropionate (PHBV) were evaluated by Brunauer-Emmett-Teller (BET), Scanning electron microscope (SEM) and Fourier-transform infrared spectroscopy (FT-IR). Short-chain fatty acids (SCFAs), dissolved organic carbon (DOC), and chemical oxygen demand (COD) equivalents were used to analyse the carbon release capacity. Results showed that agricultural waste had higher carbon release capacity than PCL and PHBV. The cumulative DOC and COD of agricultural waste were 0.56-12.65 mg/g and 1.15-18.75 mg/g, respectively, while those for synthetic polymers were 0.07-1.473 mg/g and 0.045-1.425 mg/g, respectively. The removal efficiency of nitrate nitrogen (NO3--N) were CC 70.80%, PCL 53.64%, RS 42.51%, and PHBV 41.35%. Microbial community analysis showed that Proteobacteria and Firmicutes were the most abundant phyla in agricultural wastes and biodegradable natural or synthetic polymers (BDPs). Quantitative real-time PCR (q-PCR) indicated the conversion from nitrate to nitrogen was achieved in all four carbon source systems, and all six genes had the highest copy number in CC. The contents of medium nitrate reductase, nitrite reductase and nitrous oxide reductase genes in agricultural wastes were higher than those in synthetic polymers. In summary, CC is an ideal carbon source for denitrification technology to purify low C/N recirculating mariculture wastewater.